IMPROVING COMMUNITY ECONOMY BY REVITALIZATION OF TRADITIONAL MARKET - Sekaringsih, Riswanti Budi; Marlina Wijayanti, Dwi; Muhfiatun, Muhfiatun; F. Awaliyah, Dien (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
The existence of traditional markets helps many aspects of people's lives. However, many people have turned to modern markets due to poor governance of traditional markets. Therefore, this dedication is aimed at implementing various programs that can improve the quality of it. This dedication was conducted using a community-based action service method. The results are improvements in physical and non-physical conditions such as traders' zoning, good and professional management, as well as qualified human resources for traders and market managers in order to increase the competitiveness of traditional markets. Thus, the number of consumer visits to shop at traditional markets can increase, so that it can affect the increase in the income of traders. Keberadaan pasar tradisional membantu banyak aspek kehidupan masyarakat. Meskipun demikian, sudah banyak masyarakat yang beralih ke pasar modern akibat tidak baiknya tata kelolanya. Pengabdian ini ditujukan untuk menerapkan berbagai program yang dapat meningkatkan kualitas. Dedikasi dilakukan dengan metode community-based action service. Hasilnya adanya perbaikan kondisi fisik dan non fisik seperti zonasi pedagang, manajemen pengelolaan yang baik dan profesional, pedagang dan pengelola pasar yang berkualitas mampu meningkatkan daya saing pasar tradisional. Dengan demikian jumlah kunjungan konsumen berbelanja dapat meningkat, sehingga dapat berpengaruh terhadap peningkatan pendapatan pedagang.